Research progress of risk factors and early diagnostic biomarkers of gout-induced renal injury - Wang, Sheng; Zhang, Liyun; Hao, Dongsheng; Wang, Lei; Liu, Jiaxi; Niu, Qing; Mi, Liangyu; Peng, Xinyue; Gao, Jinfang (Frontiers in Immunology, 2022)
Gout kidney injury has an insidious onset, no obvious symptoms and laboratory abnormalities in the early stages of the disease, and is not easily detected, and many cases have entered renal failure at the time of diagnosis. Therefore, the detection of gout kidney injury-related risk factors and early diagnostic biomarkers of gout kidney injury are essential for the prevention and early diagnosis of the disease. This article reviews the progress of research on risk factors and early diagnostic biomarkers of gout and kidney injury.